Improving Digital Literacy Skills With The Application Of Deep Learning Technology In Absorbing Information, Creating Information, And Evaluating And Creating Learning - Maulana, Irwan; Lengkong, Indira Krisanti; Hafidhah, Hafidhah; Madhakomala, Madhakomala (Annpublisher, 2025)
Background. Digital literacy has become the primary foundation in facing the digital era. The ability to absorb, evaluate, create, and communicate digital information is an essential competency. Aims. This research aims to describe how deep learning technology can enhance students' digital literacy skills, particularly in absorbing information, creating content, and evaluating and creating learning materials. Methods. The method employed is a qualitative documentation study. Data were obtained from academic literature, education policies, and the latest research results related to deep learning and digital literacy. Result. The results of the survey demonstrate that integrating deep learning technology in education can accelerate access to information, enhance critical thinking skills, and foster an adaptive, reflective, and data-driven learning system. Conclusion. Deep learning technology has great potential in supporting digital literacy, a primary competency of the 21st century. Implementation. The successful implementation of this technology requires systemic support to create transformative education and foster a generation of reflective, adaptive, and ethical learners.